2012
DOI: 10.1021/ac300046x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ovariectomy on Rat Mandibular Cortical Bone: A Study Using Raman Spectroscopy and Multivariate Analysis

Abstract: To investigate the effects of ovariectomy (OVX) on rat mandibular bone, the physicochemical compositions of mandibular cortical bone of ovariectomy and sham operated rats 2, 4, and 8 months after surgery were compared using Raman spectroscopy. With principal component analysis and linear discriminant analysis based on the Raman spectra, the mandibular cortical bone of the OVX group was clearly distinguished from that of the sham-operated group 8 months after surgery with no overlap. Specifically, significant r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…Fu et al 49 demonstrated how the linear discriminants of PCA separate compositional changes in the rat mandible after ovariectomy. PCA has also been used to chart developmental changes in differentiating mesenchymal stem cells 50 as well as RS signatures of cartilaginous zones during fetal femur development.…”
Section: Discussionmentioning
confidence: 99%
“…Fu et al 49 demonstrated how the linear discriminants of PCA separate compositional changes in the rat mandible after ovariectomy. PCA has also been used to chart developmental changes in differentiating mesenchymal stem cells 50 as well as RS signatures of cartilaginous zones during fetal femur development.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that higher viscoelastic energy dissipation occurs in tissue regions with a lower mineral-to-matrix ratio (Pathak et al, 2011). The mineral-to-matrix ratios of rat mandibles and lumbar vertebrae were measured to be 20 and 7.9, respectively (Fu et al, 2012; Otomo et al, 2004). In the current study, the slopes of viscosity-to-modulus curves for rat mandibles and lumbar vertebrae were found to be 1221.307 and 557.625, respectively (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It was indicated that the mineral-to-matrix ratio was lower in newly-formed bone tissue regions than in pre-existing old bone tissue regions when mouse femurs were observed under Raman spectroscopy (Pathak et al, 2011). The mineral-to-matrix ratio of bone tissue also varies depending on anatomical site (Fu et al, 2012; Otomo et al, 2004). Pathak et al (2011) found a larger viscoelastic response in a region of tissue with a smaller mineral-to-matrix ratio using nanoindentation-based dynamic mechanical analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has confirmed that Ovx leads to a significant reduction of bone mass in femurs and tibia, which are formed by endochondral ossification, but not in maxilla, which is formed by intramembranous ossification [ 12 ]. Most studies have tended to focus on the bone loss in long bone and mandibular alveolar bone after Ovx, using three-dimensional (3D) micro-computed tomography (µCT) [ 8 ], dual-energy X-ray absorptiometry (DEXA) [ 13 ], and Raman spectroscopy [ 14 ]; however, the effects of Ovx on the bone remodelling in maxilla and tibia remain unclear.…”
Section: Introductionmentioning
confidence: 99%